2013
DOI: 10.2166/aqua.2013.011
|View full text |Cite
|
Sign up to set email alerts
|

Household survey of installation and treatment efficiency of point-of-use water treatment systems in Hanoi, Vietnam

Abstract: Since urban water supply is not yet available for every inhabitant in Hanoi City, numerous residents look for alternative sources such as groundwater and rainwater to compensate the supply shortage.However, in parts of Hanoi, it was reported that groundwater is polluted by various contaminants including arsenic (As) and ammonia (NH 4 -N). Therefore, numerous types of point-of-use (POU) water treatment systems have been used in households, but treatment efficiency has not been well documented. Hence, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In water treatment plants, groundwater is treated by aeration, iron precipitation, rapid sand filtration and chlorination, whereas river water is treated by pre-sedimentation, coagulation, flocculation, sedimentation, rapid sand filtration and chlorination. In suburban and rural areas, groundwater from private tube wells is typically treated in households by sand filters (Do et al, 2014).…”
Section: Site Descriptionmentioning
confidence: 99%
“…In water treatment plants, groundwater is treated by aeration, iron precipitation, rapid sand filtration and chlorination, whereas river water is treated by pre-sedimentation, coagulation, flocculation, sedimentation, rapid sand filtration and chlorination. In suburban and rural areas, groundwater from private tube wells is typically treated in households by sand filters (Do et al, 2014).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The treatment efficacy and percent concentration changes of contaminants are presented in Figure 2 and Table 5. According to a previous study conducted in Vietnam, household RO and CP treatments can reduce iron concentrations by .45% (Do et al 2014). However, a study conducted in the USA showed that household RO devices did not effectively remove iron (Lothrop et al 2015).…”
Section: Efficacy Of Ro Devices and Cpsmentioning
confidence: 96%
“…Household water treatment practices have been recommended as a strategy to comprehensively control diarrhea (WHO 2009a). Household treatment is common in developing countries, even in urban areas where tap water is available (Do et al 2014;Shrestha et al 2018). Several studies have been conducted to examine the efficacy of locally available point-of-entry and point-of-use household treatment devices in other countries (Brown & Sobsey 2010;Mahlangu et al 2012;Do et al 2014;Li et al 2014;Lothrop et al 2015;Shrestha et al 2018).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is a principal to establish an effective policy on health and well-being protection [2]. According to the World Health Organization (WHO), between 50 and 100 l of water per person per day is needed to ensure that most basic needs are met and few health concerns arise [3]. Hence, the quality of drinking water has progressively been questioned from a health viewpoint in recent decades [4].…”
Section: Introductionmentioning
confidence: 99%